2018
DOI: 10.22146/gamaijb.26302
|View full text |Cite
|
Sign up to set email alerts
|

Does Work-Family Conflict Affect the Auditor’s Performance?: Examining the Mediating Roles of Emotional Exhaustion and Job Satisfaction

Abstract: This paper examines whether the work-family conflict (related to both work-interfering-family and family-interfering-work) of auditors affects their performance and if so, whether the effect is mediated by emotional exhaustion and job satisfaction. A mail survey is used to deliver a questionnaire to 151 auditors from ten CPA firm in Indonesia. The result shows that emotional exhaustion and job satisfaction fully mediates the relationship of work-family conflict with job performance. The result also demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 35 publications
(113 reference statements)
1
19
0
Order By: Relevance
“…When individuals or groups do a job, the quantity and quality that are obtained from their work are considered as job performance (Dinc et al, 2018;Ding et al, 2012). Some reports indicate that in organizational psychology and human resources management, the most critical parameter and content is job performance (Fisher, 2001;Springer, 2011;Yustina & Valerina, 2018). Employees' job performance in organizations is reviewed in a specific and standard time and includes their specific and discrete behaviors (Motowidlo & Kell, 2012).…”
Section: Job Performancementioning
confidence: 99%
“…When individuals or groups do a job, the quantity and quality that are obtained from their work are considered as job performance (Dinc et al, 2018;Ding et al, 2012). Some reports indicate that in organizational psychology and human resources management, the most critical parameter and content is job performance (Fisher, 2001;Springer, 2011;Yustina & Valerina, 2018). Employees' job performance in organizations is reviewed in a specific and standard time and includes their specific and discrete behaviors (Motowidlo & Kell, 2012).…”
Section: Job Performancementioning
confidence: 99%
“…Additionally, it has been postulated that emotional exhaustion is associated with work-related crisis, such as job withdrawal, dissatisfaction, and intention to leave [16]. People who suffer a high level of work-family conflict are likely to develop emotional exhaustion toward their current career [17], and emotional exhaustion is positively associated with psychological health problems [18]. Furthermore, a study has proposed that work-family conflict is significantly correlated with emotional exhaustion among female medical professionals compared with their male colleagues [19].…”
mentioning
confidence: 99%
“…As shown at Table 1, healthy lifestyle and self-compassion as independent variable has positive significant effect on auditor performance. This is consistent with reference that having healthy lifestyle and high self-compassion could improve performance (Jones et.al., 2010;Nugraha, 2017, Yustina andValerina, 2018). It can be concluded that healthy lifestyle and self-compassion are quasi moderation variables.…”
Section: Resultsmentioning
confidence: 91%
“…Two dimensions of motivational factors are internal and external motivation. Internal motivation that shaped from individual within, while external motivation is imposed by external parties or situations (Iskandar et.al,2012) Previous studies related to behavioral literature has discussed stress in the accounting profession (Yustina and Valerina, 2018). It is not surprising due to the fact that a professional accountant has one of the most stressful jobs in the financial services industry (Fogarty et al 2000).…”
Section: Introductionmentioning
confidence: 99%